(untitled) (Per Musi, 2018)
The historiographical and secondary sources help us to better understand part of the vocal aesthetics of the end of Renaissance and early Baroque. The influence of literary text - its meaning and diction –, of mother tongue, and vocal ornamentation becomes clear in the construction of the ideal vocal sound of the period. We conclude that vocal homogenization was not part of this ideal sound, that vocal ornamentation was extremely valued, and that the mother tongue greatly influenced the sound and how the vocal apparatus itself was used in the singing voice.